Color Doppler US Evaluatıon Of Hepatic And Renal Hemodynamıcs In The Cirrhosis - Serhatlıoğlu, Selami; Kocaöz, Özgür; Kırış, Adem; Uysal, Hadi; Yalnız, Mehmet; Oğur, A.y.erkin (Fırat University, 2007)
Objectives: We aimed to figure out the value of colour Doppler ultrasonography (CDUS) to determine the hepatic and renal hemodynamics in cirrhotic patients. Materials and Methods: 40 cirrhotic patients (11 Child A, 17 Child B and 12 Child C) and a control group of 20 healthy individuals were examined. Renal artery resistive index, renal artery pulsatility index, hepatic artery resistive index, hepatic artery pulsatility index, portal vein velocity, portal vein diameter and hepatic vascular index were assessed in all the individuals. The cirrhotic patients were divided into subgroups according to their Child scores and presence of ascites. The statistical differences between control group, whole and subgroups of cirrhotic patients were evaluated through these parameters. Results: Statistically, there was a significant difference regarding all the parameters between cirrhotic patients and control group and between Child C group and control group (p

Amaç: Sirozlu olgularda karaciğer ve renal hemodinamilerdeki değişiklikler açısından renkli Doppler ultrasonografinin (RDUS) değerini ortaya koymayı amaçladık. Gereç ve Yöntem: Renkli Doppler ultrasonografi ile 40 sirozlu olgu (11 Child A, 17 Child B, 12 Child C) ve renal ve hepatik fonksiyonları tümüyle normal olan 20 sağlıklı kişiden oluşan kontrol grubu incelendi. Tüm olgularda renal arter rezistif indeksi (RA-RI), renal arter pulsatilite indeksi (RAPI), hepatik arter rezistif indeksi (HA-RI), hepatik arter pulsatilite indeksi (HA-PI), portal ven hızı (PV-HIZ), portal ven çapı (PV-ÇAP) ve hepatik vasküler indeksi (HVI) değerlendirildi. Sirozlu olgular Child evrelemesi ve assit varlığına göre alt gruplara ayrıldı. Bu parametreler açısından kontrol grubu, genel sirozlu grup ve alt gruplar arasındaki istatistiksel fark değerlendirildi. Bulgular: Siroz grubu ile kontrol grubu arasında ve Child C grubu ile kontrol grubu arasında tüm parametrelerde istatistiksel olarak anlamlı farklılık mevcuttu (p
Karaciğer Sirozunda Hepatik ve Renal Hemodinamik Değişikliklerin Doppler US ile Değerlendirilmesi